Crack formation of camshaft castings: Hot tearing susceptibility and root causes. (May 2023) - Zhu, Yankang; Zhou, Kangkang; Xu, Gangqiang; Xu, Cangsu; Li, Xiaolu; Li, Yuntang; Wang, Bingqing; Oppong, Francis
Highlights: The hot tearing susceptibility of camshaft castings was studied. The Clyne-Davies model was improved. A new evaluation model of hot tearing susceptibility was proposed. Crack source was caused by excessive non-equilibrium solidification of castings. The countermeasures were proposed to reduce the probability of crack formation. Abstract: As a widely used cyclical motion component, the camshaft plays a key role in the accuracy and stability of the whole machine. Micro hot cracks in the camshaft casting process are an important cause of failure in subsequent machining and operation. In this paper, the hot tearing susceptibility of the camshaft in the casting process was studied using the alloy composition (carbon equivalent and Mn/S ratio) and mold preheating temperature. The formation mechanism of the hot tear source was analyzed through the microscopic morphology of the fracture-sensitive cross-section. Using the improved Clyne-Davies model and the newly proposed hot tearing susceptibility (HTS) model, the results show that as the carbon equivalent and Mn/S ratio increase, the hot tearing susceptibility of the camshaft first decreases and then increases. The hot tearing tendency of the casting can be reduced by appropriately increasing the mold preheating temperature. The microscopic morphology indicates that the initiation and propagation of the crack source are caused by the excessively serious non-equilibrium solidification of the camshaft metal fluid. Finally, potential countermeasures are proposed to decrease micro hot cracks in camshaft castings, including the adjustment of alloy composition, optimization of casting process parameters, and improvement of system solidification conditions.